L’enseignement inclusif destiné à des personnes souffrant de handicap physique : une idéalité à l’épreuve de la réalité - Mohamed-Amokrame Zoreli (Éducation et Socialisation)
This article examines the relationship between, on the one hand, the inclusive logic and, on the other hand and successively, the theory of complexity, solidarist ideology and the ethics of diversity. Applying this approach to the context of the University of Bejaia in Algeria which conducts inclusive activities for students who have physical disabilities, we show that by adopting a fragmentary approach, actors who engage in inclusive logic recreate at the end excluding.